দেশ ত্যাগ : সাম্প্রতিক ভাবনা - আজাদ,সালাম, 1964- (ঢাকা : সাস পাবলিকেশন্স, 1995)
Articles on Hindus and ethnic relations in Bangladesh.
In Bengali.
Keywords: Hindus -- Bangladesh; Communalism -- Bangladesh; Bangladesh -- Ethnic relations